Economic and Monetary Union in Europe and Constraintson National Budgetary Policies. (IMF Working Papers; Working Paper, 1990)
This paper reviews the pros and cons of institutionalized constraints limiting the freedom of national budgetary policies within an Economic and Monetary Union (EMU) in Europe. The issue is approached from three angles: the influence of EMU on (i) budget discipline; (ii) intergenerational equity and intertemporal efficiency; and (iii) macroeconomic stabilization. The desirability of constraints on budgetary policy is related to the arrangements for EMU-wide monetary policy, the credibility of a no-bailout clause among member states, and progress in the area of supply-side policies.